2021
DOI: 10.1038/s41531-021-00190-x
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Non-invasive vagus nerve stimulation improves clinical and molecular biomarkers of Parkinson’s disease in patients with freezing of gait

Abstract: Non-invasive vagus nerve stimulation (nVNS) is an established neurostimulation therapy used in the treatment of epilepsy, migraine and cluster headache. In this randomized, double-blind, sham-controlled crossover trial we explored the role of nVNS in the treatment of gait and other motor symptoms in Parkinson’s disease (PD) patients. In a subgroup of patients, we measured selected neurotrophin levels and markers of inflammation and oxidative stress in serum, before and after the experimental intervention. Thir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 50 publications
1
24
1
Order By: Relevance
“…9 Expression of the PDRP increases in the advancing stages of the disease but can be readily reversed by both levodopa infusion and subthalamic nucleus deep brain stimulation. 66,67 Novel noninvasive electrical stimulation of the cholinergic vagus nerve is being assessed to mitigate gait impairments in PD, [68][69][70] showing promising success in improving step time variability. 69 To that end, we speculate whether our PDGPs may be considered as a conceptual framework for future studies targeting dopaminergic treatment-resistant gait characteristics.…”
Section: Comparison With Other Reported Pd Profilesmentioning
confidence: 99%
“…9 Expression of the PDRP increases in the advancing stages of the disease but can be readily reversed by both levodopa infusion and subthalamic nucleus deep brain stimulation. 66,67 Novel noninvasive electrical stimulation of the cholinergic vagus nerve is being assessed to mitigate gait impairments in PD, [68][69][70] showing promising success in improving step time variability. 69 To that end, we speculate whether our PDGPs may be considered as a conceptual framework for future studies targeting dopaminergic treatment-resistant gait characteristics.…”
Section: Comparison With Other Reported Pd Profilesmentioning
confidence: 99%
“…It has been suggested that VNS may indirectly activate noradrenergic projections from the locus coeruleus , a region implicated in the pathogenesis of FOG, as well as exerting anti-inflammatory properties that may be important in halting disease progression. Recently, the first randomised, double-blind trial to investigate nVNS administered stimulation to the cervical vagus for 12 min each for 4 weeks in 33 PD patients with FOG ( Mondal et al, 2021 ). The authors reported positive effects on gait velocity and step length, as well as reduced duration of freezing episodes in the laboratory gait assessment circuit, though interestingly patients’ perception of their FOG-related disability (FOG-Q score) did not improve ( Mondal et al, 2021 ).…”
Section: Non-pharmacological Approachesmentioning
confidence: 99%
“…Recently, the first randomised, double-blind trial to investigate nVNS administered stimulation to the cervical vagus for 12 min each for 4 weeks in 33 PD patients with FOG ( Mondal et al, 2021 ). The authors reported positive effects on gait velocity and step length, as well as reduced duration of freezing episodes in the laboratory gait assessment circuit, though interestingly patients’ perception of their FOG-related disability (FOG-Q score) did not improve ( Mondal et al, 2021 ). Excitingly there was a significant reduction in biomarkers of inflammation [TNF-α, reduced-glutathione, and brain-derived neurotrophic factor (BDNF)] which may have implications for future disease modification trials.…”
Section: Non-pharmacological Approachesmentioning
confidence: 99%
“…Video-analysis of the FoG patients showed improvements in the time taken for turning, steps taken for turning, and steps taken for start hesitation. A follow-up crossover randomized controlled study corroborated these initial findings and showed significant improvements in walking speed, stance time and step length comparing active phase (30 days of nVNS stimulation) to sham 59 . Similarly, overall motor function (MDS-UPDRS III) also improved.…”
Section: Non-invasive Vagus Nerve Stimulationmentioning
confidence: 57%